Synthesis Of Some Fluoro Substituted Sulphonamide Benzothiazole Comprising Thiazole For Anti-Microbial Screening - V. A. JAGTAP; E. JAYCHANDRAN; G.M SREENIVASA; B.S. SATHE (International Journal of Pharma and Bio Sciences, 2010)
Some novel 3-[6’Fluoro-7’-substituted-(1’,3’)benzothiazol-2‘-yl]p-benzene sulphonamido-2-onitrobenzene (1,3) thiazolidin-4-one have been synthesized and screened for anti-microbial activity. Literature revealed that vast majority of benzothiazoles and sulphonamide compounds are known to possess pharmacologically proven therapeutic potentials. The wide range of biodynamic properties shown by fluorobenzenes 2-substituted benzothiazoles prompted us to synthesize novel compounds in hope of getting potent biodynamic agents. In the present study benzothiazole were prepared from 3-chloro-4fluoro aniline. The ortho, meta, para, nitroanilines, ortho, meta, para, chloroanilines, morpholine, piperazine, PABA, dimethyl amine, diphenyl amine derivatives of fluorobenzothiazole comprising Sulfonamido thiazole, were chosen for synthesis and pharmacological evaluation. The compounds were characterized by means of physical constants, solubility tests, TLC and by UV,IR spectral studies. This is followed by biological and pharmacological evaluation especially antimicrobial activities